Pengaruh Sistem Pengendalian Intern Pemerintah dan Aksesbilitas Laporan Keuangan Terhadap Akuntabilitas Pengelolaan Keuangan Dana Desa - Soni - Hermanto (Kajian Akuntansi, 2019)
The purpose of this research was to know the influence of internal control system and the accessibility of financial statements to accountability of village fund finance management in Merapi Timur Districts, Lahat Regency, South Sumatera. There are 13 vilalage in Merapi Timur Districts are population. Sampling in this study using saturated samples . The sample in this study was 65 people, they are the head of the village, the secretary of the village, the treasurer of the village, section head, and village consultative agency to each village in Merapi Timur District. The data was the primary data that was collected through questionnaires distributed to respondents. The data were analyzed by using multiple linear regression and supported by SPSS version 22. The results showed that partially internal control system have a positive significant effect on accountability of village fund finance management variable and the accessibility of financial statements variable have a positive significant effect on accountability of village fund finance management variable. While silmultan internal control system and the accessibility of financial statements  variable equally positive and significant influence on the accountability of village fund finance management in Merapi Timur Districts, Lahat Regency, South Sumatera